Fluorescence microscopic visualization of halophile Bacillus tequilensis CH and mixed culture of acidophilic bacteria. (December 2021) - Panda, Sandeep; Pradhan, Arun Kumar; Mishra, Srabani; Pradhan, Nilotpala
Abstract: Halophiles have been used as bioremediation agents in degradation of organic pollutants and acidophilic microorganisms are considered as efficient metal leaching agents for mineral-metal bearing wastes. In the present study, halophilic bacteria ( Bacillus tequilensis CH) and a mixed culture of acidophilic bacteria were used for their visual detection over fluorescence microscope. With regards to B. tequilensis CH, bacterial presence and its biofilm formation was studied over glass cover slips; while for the acidophilic culture, comparisons were made to observe bacterial presence over glass cover slips and a sample ore surface. It was observed that for both the microbial cultures, green fluorescence was detected at different magnifications for the bacteria as well as the biofilm formed (better visualization in case of B. tequilensis ); thus, confirming the adsorption of calcein-AM dye by the live bacterial cells. Furthermore, the 3D intensity plots, in case of the acidophiles, confirmed the presence of bacterial clusters and a possible formation of bacterial biofilm over the sample ore surface.